2017
DOI: 10.5009/gnl16231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Clinical Impact of Video Capsule Endoscopy in Patients with Chronic Diarrhea: A Korean Multicenter CAPENTRY Study

Abstract: Background/AimsIn some cases, chronic diarrhea is unexplained, and small bowel disorders may be one of the causes. The aim of this study was to assess the diagnostic yield and clinical impact of video capsule endoscopy (VCE) in patients with chronic diarrhea.MethodsWe retrospectively analyzed records from October 2002 to August 2013 in the VCE nationwide database registry (n=2,964). Ninety-one patients from 15 medical centers (60 males and 31 females; mean age, 47±19 years) were evaluated for VCE as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…Current data suggest that CE should not be the first-line diagnostic test [19,20]. Song et al, demonstrated the positive diagnostic yield of CE (42.9%) in patients with chronic diarrhea, in whom the final diagnosis changed in 31.4% of patients, with Crohn’s disease being the most common finding [21]. In a systematic review of CE and unexplained chronic abdominal pain, a limited diagnostic yield of 20.9% was described.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that CE should not be the first-line diagnostic test [19,20]. Song et al, demonstrated the positive diagnostic yield of CE (42.9%) in patients with chronic diarrhea, in whom the final diagnosis changed in 31.4% of patients, with Crohn’s disease being the most common finding [21]. In a systematic review of CE and unexplained chronic abdominal pain, a limited diagnostic yield of 20.9% was described.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this study was to evaluate the PCC system functionality in established and suspected IBD subjects. Secondary objectives included reader assessments of PCC coverage of the SB and colon, overall study reading time, capsule video quality, and safety of the system, all of which were conducted by answering a subjective questionnaire 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Although CE is not recommended as a first-line examination for diarrhea, it facilitates making the diagnosis in 9% of patients with negative conventional endoscopy and imaging examination results [ 35 ]. The most common cause is IBD, and hematochezia and hypoalbuminemia on CE are positive predictors for it [ 36 ]. There is a lack of clinical studies on CE for patients with dyspepsia, constipation, high level CA 19-9, and abdominal distention, especially in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%